IMPACT OF COVID-19 ON EXTERNAL LABOR MIGRATION OF UKRAINIANS - BOKOVETS, VICTORIA; DAVIDYUK, LYUDMILA; OLIINYK, OKSANA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
According to the International Labor Organization (ILO), there are about 164 million migrant workers in the world. This shows that the main motive for the migration movement is job search. About three-quarters of all migrant labor flows come from high-income countries, where one in six workers is an immigrant. Conversely, the highest level of emigration is from those areas that have a high level of poverty and virtually no social protection. The spread of the coronavirus has led to the rapid closure of national borders, and the vast majority of migrant workers have found themselves without income and in difficulty, prompting the ILO to call the situation a "crisis within a crisis."The COVID-19 pandemic has had a negative impact on migrant workers, regardless of their job status and qualifications. While workers in the hotel and restaurant and retail sectors lost their jobs, those employed in health care and agriculture, on the contrary, were in demand and at risk of infection. Thus, the pandemic has sharply exacerbated the scale, degree of risk and uncertainty inherent in migrant workers, leading to even greater vulnerability.The article examines the impact of COVID-19 on the scale of external labor migration of Ukrainians and its economic and social consequences for the country. The peculiarities of international labor migration in the conditions of COVID-19 are clarified and probable prospects of transformation of migration tendencies are determined.Most migrants are currently in a state of uncertainty. On the one hand, they are temporarily cut off from foreign earnings, on the other hand, even in conditions of impossibility of migration, they are not interested in vacancies offered on the labor market of Ukraine. Based on the above study, we can conclude that most likely in the near future the volume of emigration will remain at the current level, and if the economic downturn continues, the number of emigration flows from Ukraine will increase.
Keywords: external labor migration; pandemic; emigration; immigration; consequences of migration